Using brefeldin A to disrupt cell wall polysaccharide components in rice and nitric oxide to modify cell wall structure to change aluminum tolerance - Yan, Jianchao; Zhu, Jiandong; Zhou, Jun; Xing, Chenghua; Song, Hongming; Wu, Kun; Cai, Miaozhen (Frontiers in Plant Science, 2022)
The composition and structure of cell wall polysaccharide is tightly correlated with aluminum (Al) toxicity and tolerance for plants. Nitric oxide (NO) is a vital signal molecule in response to Al toxic action since NO affects Al accumulation via regulating cell wall composition and oxidative damage. The present study is to explore if NO is involved in modifying and assembling at cell wall structure construction, then altering rice Al tolerance. Brefeldin A (BFA), a macrolide, is used to disrupt cell wall polysaccharide components, and sodium nitroprusside (SNP), NO donor, is used to modify wall polysaccharides. Their functions were identified by analyzing Al accumulation, polysaccharides in the cell wall, and chemical groups with FTIR. Pretreatment with BFA increased Al-induced inhibition of Al accumulation in root tips and root elongation of two rice genotypes of Nipponbare and Zhefu 802, as well as significantly decreased the polysaccharide content including pectin, hemicellulose 1, and hemicellulose 2, indicating that BFA inhibits the biosynthesis of components in the cell wall and makes the root cell wall lose the ability to resist Al. The addition of SNP significantly alleviated toxic effects of Al on root growth, Al accumulation and oxidative damage, and decreased the content of pectin polysaccharide and functional groups of hydroxyl, carboxyl, and amino in cell wall, while had no significant effect on hemicellulose 1 and hemicellulose 2 content compared with Al treatment. Furthermore, NO can’t reverse the inhibition of BFA-induced polysaccharide biosynthesis and root growth. NO may be a downstream signaling molecule in wall structure conduction via modifying physiochemical characteristics of pectin and the functional groups, thereby affecting cell wall assembly and structure for Al tolerance.